Magnetically activated carbon fibers felt (MACFF) as an effective adsorbent for successful removal of cephalexin and amoxicillin from water - Ali Maghsoudi; Alireza Khajeh-Amiri (Results in Chemistry)
This study used magnetically activated carbon fiber felt (MACFF) prepared by solvothermal reaction as efficient adsorbents for removing cephalexin and amoxicillin antibiotics. X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) analysis confirmed the presence of Fe3O4 (magnetite) on the activated carbon fiber felt (ACFF) surface. The BET results showed that the deposition of Fe3O4 on the surface of ACFF reduced the specific surface area to 108 m2/g. A combination of kinetic and thermodynamic studies was then performed to evaluate the absorption behavior of MACFF in the presence of cephalexin and amoxicillin as drug wastes. The maximum MACFF dose for cephalexin and amoxicillin was 100 mg/g and 20 mg/g, respectively. Thermodynamic studies show that the adsorption process is spontaneous for both antibiotics but was endothermic for cephalexin adsorption and exothermic for amoxicillin adsorption. The second-order pseudo-model was the best model obtained from the kinetic studies. Notably, ampicillin had a negligible tendency to be adsorbed on MACFF. The adsorption of cephalexin, amoxicillin, and ampicillin on the MACFF was also studied by the XPS analysis, demonstrating the interaction between cephalexin and amoxicillin with the surface of MACCF. In this work, magnetization is an effective method to improve the surface properties of ACFF and successfully remove the antibiotics cephalexin and amoxicillin, but not ampicillin. Thermodynamic studies indicate a spontaneous process of adsorption of both antibiotics, which is exothermic for amoxicillin adsorption and endothermic for cephalexin adsorption.